2017
DOI: 10.1007/s00784-017-2184-1
|View full text |Cite
|
Sign up to set email alerts
|

Glass ionomer cement inhibits secondary caries in an in vitro biofilm model

Abstract: Glass ionomer cements have a higher secondary caries inhibiting effect than resin composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 38 publications
0
38
0
2
Order By: Relevance
“…As shown in this study, adding excess GIC liquid results in a mechanically fragile material . Moreover, the clinical durability of the GIC depends on the resistance of the material and on its biocompatibility, mainly related to its chemical adhesion and ability in fluoride release …”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…As shown in this study, adding excess GIC liquid results in a mechanically fragile material . Moreover, the clinical durability of the GIC depends on the resistance of the material and on its biocompatibility, mainly related to its chemical adhesion and ability in fluoride release …”
Section: Discussionmentioning
confidence: 80%
“…Another important property of GIC, which differentiates this material from any other material, is its ability to release fluoride and its consequent effect on inhibiting secondary caries . The cycle of demineralization and remineralization applied in this study simulates the pH cycling that occurs during the formation of dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12] The antibacterial activity of glass ionomer cements (GIC) is mostly attributed to their fluoride and other ions release for secondary caries inhibiting effect, which has been already confirmed in vitro with lower demineralization depths of the glass ionomer groups adjacent to the dental hard tissue. [13][14][15][16][17][18][19] Thus, these cements are expected to actively control microbial biofilm formation, while biofilms modulate the release of fluoride from GICs. 20,21 On the other hand, studies have shown that fluoride-releasing activity of GICs is insufficient for effective protection.…”
Section: Introductionmentioning
confidence: 99%